Dhammacakka : the Source of High Morality - Phanchan, Promphisit; Thawee (Thanawaro), Sirirattananuwat (Mahachula Academic Journal, 2025)
This article is studied on the discourse of Dhammacakkappavattanasutta regarded as the high moralities. Its process is done through the avoidance of 2 extreme ways, i.e. Kãmasukkhallikãnuyoga and Attakilamathãnuyoga being become the Middle Path between the 2 extremes ways, namely;- the Eightfold Path. It gives vision, it gives knowledge and it leads to calm, to insight, to enlightenment, to Nibbãna. The Middle Path is related with Threefold training, i.e. Sĩla, Samãdhi, Paññã. The Sĩla is the base of Samãdhi, the Samãdhi is the base of Paññã, the Paññã is the base of Citta and then the transmittance to the eradication of all defilements leading to the highest goal of Buddhism as Nibbãna. The Dhammacakka delivered by the Lord Buddha who aims to give new knowledge factor of Dhamma found by oneself to Pañcavaggĩ through the word of “Enlightenment”. The Lord Buddha clearly realizes the Four Noble Truths in these three aspects, in these twelve ways. The Lord Buddha claims to have realized the perfect Enlightenment that is super in the world with its gods, with its Mãra and Brãhma, in this world with its recluses and Brahmanฺa, with its princes and men. After the First Sermon, the Lord Buddha can get the first noble follower as Sotãpanna, i.e. Koṇdฺañña. From that, the Lord Buddha preaches next other discourses to remaining Pañcavaggĩ with upasok Yasa group and then the Holy One (Arahanta) arise in the first year for the numbers of 60. The Lord Buddha gives the ideal of Dhamma Communication in the first speech to those noble followers i.e. “Caratha Bhikkhave Cãrikamํ Bahujanahitãya Bahujanasukkhãya Lokãnukampãya...”. As above mentioned, Buddhism has been going to Suvanฺnฺabhũmĩ, in the Southeast Asia, Thailand, Myanmar etc. and to the western countries as appeared in the present time.